The Legal Aspect of the Tax Competition in EU: Case of Kosovo - Fitore Gezim Morina (Sriwijaya Law Review, 2019)
The aim of this paper is to analyse the tax competition -fiscal competition within the EU Member States. The complexity of the tax competition concept in the EU will be addressed in two dimensions: the impact of tax competition on the growth of foreign investments and the increase of revenues that preserves the neutrality of common market. In the case of the functioning of tax competition, the Kosovo tax system will be compared to the tax system of the EU. Compilation qualitative methods, individual case study methods, and normative analysis methods were applied in this study. From the results of the treatment one may notice that through increased tax competition, the attractiveness of their tax systems increases automatically through the provision of lower tax rates that may result in foreign investment inflows. Given that resident and non-resident persons within the jurisdiction of a State have equal treatment from a fiscal point of view. It is concluded that the principle of neutrality is fully implemented in the EU Member State and those that express aspirations for joining the EU. The current changes in the tax system of Kosovo, made the system more competitive within the EU area